Disorientations: The Political Ecology of “Displacing” Floating Communities from Cambodia's Tonle Sap Lake - Chann S; Beban A; Flaim A; Gorman T; Vouch LL (Wiley, 2024)
In this article, we extend a theory of disorientations to reveal how attempts to fix and control both water and people are disrupting once-fluid relationships between the Tonle Sap Lake and communities who have lived with-on the lake for generations. Using ethnographic and participatory mapping methods, we examine the socio-ecological dynamics that preceded and succeeded in the forced relocation of three floating communities in 2018. We argue that communities’ experiences challenge land-centric and event-centric understandings of displacement that pathologise fluid lifeways and fail to account for the materiality of water that has shaped floating villages’ multi-generational relationships with their wetland ecology. We develop the concept of disorientations to illuminate villagers’ experiences of relocation within a collapsing aquatic ecosystem—a collapse catalysed by state efforts to impose fixity on both hydrological flow and community mobility. The lens of disorientations invites displacement debates to consider materialities of place—whether pulsing water or living, shifting soils.
Keywords: disorientation; displacement; materiality; water; Tonle Sap Lake; Cambodia